Formulation and characterisation study of paper concrete: a futuristic building material - Selvaraj, R.; Bhuvaneshwari, B. (Journal of Structural Engineering, 2025)
Conventional building materials are beyond the reach of majority of the world population due to their poor affordability. This is due to escalation of cost of building materials and other reasons. In this paper an attempt is made to utilize waste papers in concrete with and without mineral admixtures like, fly ash, kaolin, rice husk ash (RHA), and clay. The characterization study such as cylinder compressive strength, splitting tensile strength, water absorption and dry density were carried out and the behaviour of this new material “Paper Concrete” is assessed. It is also found that the incorporation of clay in the mix improves strength properties in paper concrete. It is a light weight material with large amount of energy absorption characteristics and thus it can be a promising futuristic building material.